Gene Expression Analysis Suggests Immunological Changes of Peripheral Blood Monocytes in the Progression of Patients With Coronary Artery Disease - Wang, Chunyue; Song, Chenxi; Liu, Qianqian; Zhang, Rui; Fu, Rui; Wang, Hao; Yin, Dong; Song, Weihua; Zhang, Haitao; Dou, Kefei (Frontiers in Genetics, 2021)
Objectives To analyze the gene expression profile of peripheral blood monocytes in different stages of coronary artery disease (CAD) by transcriptome sequencing, and to explore potential genes and pathway involved in CAD pathogenesis. Methods According to the screening of coronary angiography and quality control of blood samples, eight intermediate coronary lesion patients were selected, then eight patients with acute myocardial infarction, and eight patients with normal coronary angiography were matched by age and gender. Transcriptomics sequencing was conducted for the peripheral blood monocytes of these 24 samples by using the Illumina HiSeq high-throughput platform. Then, differentially expressed genes (DEGs) were analyzed. Gene Ontology (GO) functional annotation, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway annotation, and protein-protein interaction (PPI) network were applied to annotate the potential functions of DEGs. Results Compared with the normal coronary angiography group, we identified a total of 169 DEGs in the intermediate coronary lesion group, which were significantly enriched in 59 GO terms and 17 KEGG pathways. Compared with the normal coronary angiography group, we found a total of 2,028 DEGs, which were significantly enriched in 311 GO terms and 20 KEGG pathways in the acute myocardial infarction group. The cross-comparison between normal versus intermediate coronary lesion group, and normal versus acute myocardial infarction group included 98 differential genes with 65 up regulated and 33 down regulated genes, which were significantly enriched in 46 GO terms and 10 KEGG pathways. During the progression of CAD, there was a significant up-regulated expression of CSF3, IL-1A, CCR7, and IL-18, and down-regulated expression of MAPK14. Besides GO items such as inflammatory response was significantly enriched, KEGG analysis showed the most remarkable enrichments in IL-17 signaling pathway and cytokine-cytokine receptor interactions. Conclusions Transcriptomics profiles vary in patients with different severity of CAD. CSF3, IL-1A, CCR7, IL-18, and MAPK14, as well as IL-17 signaling pathway and cytokine and cytokine receptor interaction signaling pathway related with inflammatory response might be the potential biomarker and targets for the treatment of coronary artery disease.